P30 Efficacy of pulsed cyclophosphamide and methyl-prednisolone therapy in patients with progressive interstitial lung disease. (12th November 2015) - Dutta, P; Avery, P; Mansell, L; Griffiths, B; Forrest, I; Simpson, AJ
Abstract : Introduction: Therapeutic options for progressive interstitial lung disease (ILD) are limited, as no pharmacological intervention has been shown to improve mortality significantly. Intravenous (IV) pulsed cyclophosphamide and methyl-prednisolone are administered in some centres for rapidly progressive ILD, based on small clinical improvements in patients with ILD secondary to systemic sclerosis. We studied the outcome of patients with ILD who received IV cyclophosphamide and methyl-prednisolone therapy in our centre. Methods: Patients were identified from a database of those receiving cyclophosphamide. We reviewed the case notes of patients receiving IV cyclophosphamide between January 2010 to August 2014, comparing the rate of change in forced vital capacity (FVC) and transfer factor for carbon monoxide (TLco) before and after therapy. Adverse events were also recorded. Results: Records from 53 patients with a mean age of 60 years (range 39 – 81 years) were reviewed; 29 (55%) were male. Diagnosis included Connective Tissue Related-ILD (21), Idiopathic NSIP (12), Chronic Hypersensitivity Pneumonitis (8), IPF (6) and Undifferentiated-ILD (6). The median number of cyclophosphamide pulses received was 6 (range 1 to 23). After completion of cyclophosphamide, 41 (77%) patients received follow on immunosuppressive therapy in the form of mycophenolate mofetil (37 patients), azathioprine or rituximab. The average rate of change of lung function was significantly less after cyclophosphamide therapy both for FVC (Figure 1 ) p = 0.0004 and TLco p = 0.00015. Whilst on therapy 8 (15%) patients had bone marrow suppression (new onset neutrophil count <2.0 × 10 9 /l and/or platelet count <140 × 10 9 /l), 4 (7%) had elevated liver function tests, 3 (6%) had abnormal renal function, and one was investigated for microscopic haematuria. 32 episodes of infections were documented of which 21 were of respiratory origin. 25 (71%) out of 35 patients who suffered from an adverse event were able to complete therapy. Conclusion: In our single centre, retrospective study, pulsed intravenous cyclophosphamide and methyl-prednisolone was associated with stabilisation of lung function in a mixed cohort of patients with progressive ILD. Adverse events were common but transient and managed with dose reduction and/or delayed schedule.